2002
DOI: 10.1016/s0031-0182(02)00252-3
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing daily temperatures from growth rates of the intertidal bivalve mollusk Chione cortezi (northern Gulf of California, Mexico)

Abstract: We establish a model for the reconstruction of average daily sea surface temperatures from calcification rates of an intertidal bivalve mollusk. The rate of shell production in Chione cortezi (Carpenter, 1864, ex Sloat MS) is mainly controlled by water temperature, ontogenetic age and the effect of tidal cycles. Statistical methods developed by dendrochronologists can successfully extract the water temperature signal from daily growth increment chronologies. After removal of noise, the growth rates are express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…Of these factors, seawater temperature of the habitat has been regarded as the most important control on shell growth (e.g. Kennish 1980, Jones et al 1989, Goodwin et al 2001, Schöne et al 2002. Our study confirms that the duration of the shell growing season and the lunar day shell growth rate of Phacosoma japonicum in Tokyo Bay are primarily controlled by seawater temperature (Schöne et al 2003).…”
Section: Environmental Parameters Controlling the Shell Microgrowth Psupporting
confidence: 82%
See 1 more Smart Citation
“…Of these factors, seawater temperature of the habitat has been regarded as the most important control on shell growth (e.g. Kennish 1980, Jones et al 1989, Goodwin et al 2001, Schöne et al 2002. Our study confirms that the duration of the shell growing season and the lunar day shell growth rate of Phacosoma japonicum in Tokyo Bay are primarily controlled by seawater temperature (Schöne et al 2003).…”
Section: Environmental Parameters Controlling the Shell Microgrowth Psupporting
confidence: 82%
“…Only a few studies have made use of variable shell growth rates (sclerochronology) as proxies for environmental conditions such as daily water temperature (e.g. Schöne et al 2002Schöne et al , 2003Schöne et al , 2006. One of the main problems for the latter approach is that many different, complexly interacting environmental and physiological processes may exert control over shell growth rates.…”
Section: Introductionmentioning
confidence: 99%
“…It also enables precise calibration of geochemical tracers during the growth period (see Schöne et al, 2002), to a degree not typically possible with other species (e.g. Wanamaker et al, 2007;Beirne et al, 2012).…”
Section: Used the Manila Clam (Venerupis Philippinarum)mentioning
confidence: 99%
“…Partitioning of oxygen isotopes between molluscan shells and seawater has historically been assumed to closely approximate in isotopic equilibrium (Witbaard et al, 1994;McConnaughey et al, 1997;Hickson et al, 1999;Schöne et al, 2002;Schöne, 2003). On the other hand more recently Owen et al (2002a, b) showed in a thorough laboratory study a positive deviation from equilibrium ( + 0.6x ) in Pecten maximus.…”
Section: Age and Growth In Aequipecten Opercularismentioning
confidence: 99%